Wage, Price and Unemployment Dynamics in the Spanish Transition to EMU Membership - Katarina Jusélius; Javier Ordó\~nez (Kiel Institute for the World Economy (IfW), 2008)
This paper provides an empirical investigation of the wage, price and unemployment dynamics that have taken place in Spain during the last two decades. The aim of this paper is to shed light on the impact of the European economic integration process on Spanish labour market and the convergence to a European level of prosperity. We find some important lessons to be learnt from the Spanish experience that should be relevant for the new member states. Second, before fixing the real exchange rate it seems crucial that it is on its sustainable (competitive) purchasing power parity level. First, high competitiveness in the tradable sector seems crucial for the real and nominal convergence to be successful. The increase in consumption wages and consumer prices as a result of the Balassa-Samuelson effect should not be allowed to exceed the improvement in productivity. Second, before fixing the real exchange rate it seems crucial that it is on its sustainable (competitive) purchasing power parity level. Third, there does not seem to be a short-cut to a European level of standard of living: the path to sustainable prosperity seems to follow the path of productivity improvement. Forth, excessive real wage increases seem to lead to increasing unemployment, slowdown in productivity growth, higher interest rates, and loss of competitiveness. On the other hand, the access to the European market and the possibility of increased export demand is likely to speed up the convergence process as long as competitiveness is not eroded by excess wage increases.
Keywords: E24; C32; 330; Balassa-Samuelson effect; nominal and real convergence; unemployment dynamics; purchasing power parity; cointegrated VAR; Europäische Wirtschafts- und Währungsunion; EU-Erweiterung; Wirtschaftliche Anpassung; Entwicklungskonvergenz; Arbeitslosigkeit; Beschäftigungseffekt; Balassa-Samuelson Effekt; Kaufkraftparität; Lohnniveau; Inflation; Spanien